1957
DOI: 10.1111/j.1423-0410.1957.tb03958.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased Destruction of “Compatible” Red Cells

Abstract: Summary Increased red cell destruction after intravenous injection of apparently compatible red cells was observed in a healthy individual. No circulating antibodies could be demonstrated in the serum by means of the usual serological techniques. Résumé Il a été trouvé chez un individu normal une vitesse accrue d'élimination de globules rouges injectés par voie intraveineuse, ceci malgré qu'il fût impossible de trouver par les techniques sérologiques courantes des anticorps contre ces globules dans le sérum de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
8
0
2

Year Published

1958
1958
1979
1979

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 1 publication
3
8
0
2
Order By: Relevance
“…In this respect there is a great similarity to the cases reported by Adner and Sjölin [1], Jandl and Greenberg [4], Temperly and Sharp [7], Goudsmit and Krijnen [2]. In all the patients described the red cells of the first transfusion appeared to survive normally for about two weeks after which there was rapid destruction, whereas the red cells from subsequent transfusions were rapidly destroyed from the beginning.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In this respect there is a great similarity to the cases reported by Adner and Sjölin [1], Jandl and Greenberg [4], Temperly and Sharp [7], Goudsmit and Krijnen [2]. In all the patients described the red cells of the first transfusion appeared to survive normally for about two weeks after which there was rapid destruction, whereas the red cells from subsequent transfusions were rapidly destroyed from the beginning.…”
Section: Discussionsupporting
confidence: 53%
“…Similar cases were described by Jandl and Greenherg [4], Goudsmit and Krijnen [2], Adner and Sjölin [1], Temperley and Sharp [8].…”
supporting
confidence: 64%
“…Previous findings [19] that in vitro weak antibodies may cause rapid red cell destruction indicates that some of the AA positive and manual negative antibodies may be clinically important. Furthermore, several authors [4,6,8,9,11,27,29,30] have reported hemolytic transfusion reactions or accelerated destruc tion in vivo of 'apparently' compatible cells.…”
Section: Discussionmentioning
confidence: 99%
“…Fudenberg et Allen [7] ont en effet montré que l'on peut observer dans ces conditions un temps de survie considérablement diminué, alors que les méthodes sérologiques les plus sensibles ne détectent plus l'anticorps. Goudsmit et Krijnen [8] et Adner et Sjolin [1] ont observé des faits voisins. De toutes façons, la transfusion d'un tel sang peut réaliser une réactivation de l'anticorps et, au fur et à mesure de sa production, les globules transfusés sont détruits: c'est ce qui explique l'augmentation de la bilirubine indirecte dans le sang de notre malade n° 6, et le subictère constaté quelques jours après les transfusions de sang comportant l'antigène S (tableau XI).…”
Section: ° Difficulté Du Diagnostic Sérologique Après Un Accident D'unclassified